THE EFFECT OF USING FISH OFFAL FERMENTATION MEDIUM CRUDE ENZYME BROMELAIN WHICH GIVEN THE QUALITY OF SOY SAUCE AND SALT CATFISH - Jekson Alatas K. Sianturi; Syahrul '; Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research aimed to evaluate the effect of adding to the quality of fish offal sauce catfish asfermentation medium. fish offal as much as 800 grams and 400 grams of catfish fillet meatobtained from one of the markets in Pekanbaru. Fish offal will be fermented for 4 days byadministering a combination of 4 different types of salt and crude enzyme bromelain which is A1(salt 20% and 20% crude enzyme bromelain), A2 (salt 20% and 30% crude enzyme bromelain),A3 (salt 30% and 20% crude enzyme bromelain), A4 (salt 30% and 30% crude enzymebromelain). Solution of fermented fish offal will be used as a fermentation medium to view theeffect on the quality of pangasius fish sauce enzymatically for 3 days. the quality of the finalproduct was observed on organoleptic, protein content, NPN levels, pH levels, and total bacterialcolonies. the results of research showed that the combination of salt 30% and 20% crude enzymebromelain to be the best in the organoleptic test on the value of color and odor. While, theprotein levels A2 to be the best treatment and the levels of NPN A3 is the best treatment and thetotal value of bacterial colonies on the A1 treatment had the highest colony plate count. Fishsauce contains: a minimum of 2% protein, 102 APM coliform bacteria / g, total plate count 103colonies / g.